ANALISIS KESULITAN BELAJAR MATEMATIKA UNTUK MATERI OPERASI BILANGAN PECAHAN DI SMP NEGERI KEWAPENTE - Selfina Fridoline Meyana; Gregorius Taga; Hilaria Melania Mbagho (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
The purpose of the study was to determine the value of learning difficulties for grade VII B students of SMP Negeri Kewapante in solving fractional operations problems. The type of research used is a qualitative research which aims to obtain an actual picture of students' difficulties in solving fractional operations problems in class VII B SMP Negeri Kewapante. The research subjects were students of class VII B who had learning difficulties seen from the scores obtained did not reach the KKM. Data was collected by using test and interview methods. The data analysis technique used in this research is descriptive statistical analysis. The results showed that there were 4 students who had difficulty in solving fractional number operations. Efforts that can be made are creating a conducive classroom atmosphere, increasing practice questions, holding group discussions, and giving backtests. From the efforts made above, students who have learning difficulties experience changes and an increase in learning outcomes